Impact of social media use on job performance of private university teachers in Henan Province, China - Jun, Gao; Hussin, Wan Nur Tasnim Binti Wan (Edelweiss Applied Science and Technology, 2025)
This paper studies the impact of social media use (SMU) on the job performance of teachers in private universities in Henan Province, providing practical guidance for the management and career development of teachers. Specifically, this study distinguishes the impact of social-oriented (SO-SMU) and job-oriented (JO-SMU) on teachers’ research performance and teaching performance, respectively. This study collected data from 286 respondents from multiple private universities in Henan Province through a questionnaire survey and used quantitative analysis methods and SPSS to conduct reliability, validity, and correlation analysis on the data. Finally, linear regression was used to explore the relationship between variables. The study found that both SO-SMU and JO-SMU have a significant positive impact on teaching performance. However, both SO-SMU and JO-SMU have a certain negative impact on research performance. Excessive or improper SMU will distract teachers from scientific research activities, resulting in a decrease in scientific research efficiency. Therefore, teachers in private universities in Henan Province should actively use social media to improve their teaching performance. At the same time, university teachers should also reduce the negative impact of social media on scientific research performance, consider changing the way social media is used, and explore other channels to improve scientific research.